Estimation of Serum Uric Acid Levels in Bangladeshi Gestational Diabetic Mothers Attending a Tertiary Care Hospital - Mishu, Farzana Akonjee; Muttalib, MA; Yesmin, Mst Shaila; Sultana, Gazi Sharmin; Ferdous, Nadia; Shamsunnahar, - (BIRDEM Medical Journal, 2019)
Background: The hyperuricaemia in gestational diabetes mellitus (GDM) has been explained to be a component of the metabolic syndrome which reflects insulin resistance. Gestational huperuricaemia was found to be significantly associated with a high rate of maternal and foetal complications along with proteinuria and hypertension. Aims of this study were to evaluate the serum uric acid levels in Bangladeshi women with GDM in their second and third trimesters of pregnancy. Methods: This descriptive cross-sectional study was conducted at Mymensingh Medical College Hospital from July 2013 to June 2014. Pregnant women, in their second and third trimester, attending the outpatient department of Obstetrics and Gynecology and the Department of Endocrinology were enrolled by purposive sampling technique. GDM was diagnosed on the basis of oral glucose tolerance test (OGTT) as defined in WHO criteria 2013. Results: Out of 172 participants, 86 had GDM (case) and 86 were normoglycemic (control). The mean age of GDM and control groups was 28.6±3.2 years and 27.3±3.1 years respectively. The BMI was 26.4±1.5 kg / m 2 and 26.3±1.3 kg / m 2. In this study we found serum uric acid levels in GDM and without GDM were 4.47±0.42 mg/dl and 4.48±0.41 mg/dl respectively (p>0.05). Serum uric acid level in GDM group was significantly (p<0.001) higher in third trimesters (4.48 ±0.41 mg/dl) compared to those without GDM (3.52 ±0.74 mg/dl). Conclusion: There was distinct alteration of serum uric acid level in GDM compared to normal pregnancy. Estimation of serum uric acid levels might be incorporated in every GDM cases for prevention of complications. Birdem Med J 2019; 9(1): 55-58